Loans to small industries and small borrowers - Sudarshan Lal (New Delhi : Navrang, 1976)
The book discusses in brief the eligibility of small industries and various categories of small borrowers for grant of credit facilities .
obn23/01/2019
Loans
Keywords: Bank loans; Banks and banking-India; Banks and banking